2024
DOI: 10.3390/microorganisms12020272
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Changes in Experimental Model of Long COVID

Hussain Hussain,
Michael J. Paidas,
Ramamoorthy Rajalakshmi
et al.

Abstract: The coronavirus disease-19 (COVID-19) pandemic, declared in early 2020, has left an indelible mark on global health, with over 7.0 million deaths and persistent challenges. While the pharmaceutical industry raced to develop vaccines, the emergence of mutant severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) strains continues to pose a significant threat. Beyond the immediate concerns, the long-term health repercussions of COVID-19 survivors are garnering attention, particularly due to documented case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…B,E,H,K,N,Q). inoculated mice treated with 5 mg/kg SPIKENET (SPK) eased all of these changes (C,F (H&E original magnification is 400× for (A-O) and 66× for (P-R)) [8,13,21].…”
Section: Protective Effect Of Spk On Organs During Chronic Infectionmentioning
confidence: 99%
“…B,E,H,K,N,Q). inoculated mice treated with 5 mg/kg SPIKENET (SPK) eased all of these changes (C,F (H&E original magnification is 400× for (A-O) and 66× for (P-R)) [8,13,21].…”
Section: Protective Effect Of Spk On Organs During Chronic Infectionmentioning
confidence: 99%
“…The published evidence suggests that long COVID patients, even those who experienced less severe or even asymptomatic diseases, may have a prolonged inflammatory response [103], probably coupled with viral reactivation and/or immune dysregulation able to prevent the resolution of cutaneous manifestations [104]. Recently, using a murine model, Hussain et al reported a marked absence of hair follicles, the destruction of adipose tissues, and the obliteration of the epidermal layer as long-term post-COVID-19 cutaneous effects [105].…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…The complete destruction of hair follicles is thought to be attributable to several factors, including the direct effect of the virus, the influence of Transforming Growth Factorβ (TGF-β) [106], and changes in the androgen receptor content of dermal papilla [107]. It is noteworthy that Hussain and colleagues [105] demonstrated that treatment with a newly identified 15-amino-acid synthetic peptide, SPIKENET (SPK), which can prevent Spike glycoprotein-1 from binding with host receptors and promote an anti-inflammatory response, successfully restored the above-mentioned long COVID dermatologic changes. This finding suggests that SPK may be considered as a potential therapeutic strategy to prevent long-term cutaneous alterations caused by SARS-CoV-2, thus ameliorating skin disease progression related to COVID-19.…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…Livedo reticularis [113,114] Petechiae and purpura [112,[114][115][116] Similarities to chickenpox or herpes infection Vesicular rash [117,118] Discoloration of the toes and fingers to red or purple, swelling, Pain COVID toes [118] Maculopapular rash, urticarial lesions, chilblains [119] Skin rashes [38] Absence of hair follicles, destruction of adipose tissue, damage to the epidermal layer Persistent cutaneous extracutaneous symptoms [120][121][122] Livedo reticularis lesions, petechiae, painful acral red purple papules, Maculopapular exanthem (morbilliform), papulovesicular rash, urticaria, [123] Morbilliform eruptions, urticaria, papulosquamous eruptions [120] Pernio lesions [119]…”
Section: Dermatological Complicationsmentioning
confidence: 99%
“…Huang et al have studied 1655 hospitalized Chinese patients 6 months after infection onset and reported that only 47 patients (3%) had reported skin rashes [38]. In addition, other information on long term COVID-19 have declared persistent cutaneous and extracutaneous symptoms such as absence of hair follicles, destruction of adipose tissue, damage to the epidermal layer [120][121][122].…”
Section: Long Covid-19 and Dermatological Complicationsmentioning
confidence: 99%